Streptomyces: isolation, optimization of culture conditions and extraction of secondary metabolites - Khattab, Ahmed I.; Babiker, Eltahir H.; Saeed, Humodi A. (International Current Pharmaceutical Journal, 2016)
The objectives of this study were to isolate and identify Streptomyces from soil sediments as well as to optimize cultural growth conditions for maximum antibacterial productivity. A total of fifty soil sediments were collected from Red Sea, Sudan. The soil sediments were pretreated and cultivated on agar medium. Promising Streptomyces spp. were isolated by agar overlay method using indicator organisms. Optimization of chemical and physical culture conditions was carried out. The later was judged by assessment of antibacterial activity. Ethyl acetate was used to extract the secondary metabolite compounds. The separation of the active ingredients was performed using both thin layer chromatography (TLC) and gas chromatography-mass spectrometer (GC-MS). The results revealed nine strains of Streptomyces. Of them two (PS1 and PS28) isolates exhibited high activity against pathogenic bacteria. The optimum growth conditions were pH 7.5, temperature at 30°C, soyabean concentration 2.5 g/l, incubation period in 7 days, MgSO4.7H2O conc. 1g/l and K2HPO4 conc. 2.5g/l. TLC test showed three and two fragments from metabolites of PS1 and PS28 respectively, while the GC-MS analysis revealed eight and eleven compounds with antibacterial activity of PS1 and PS28 respectively. It is concluded that marine is promising source of secondary metabolites. Khattab et al., International Current Pharmaceutical Journal, February 2016, 5(3): 27-32